Atlanta Unbound : Enabling Sprawl through Policy and Planning - Basmajian, Carlton Wade, 1973- (Urban life, landscape, and policy., 2013)
Looking at Atlanta, Georgia, one might conclude that the city's notorious sprawl, degraded air quality, and tenuous water supply is a result of a lack of planning-particularly an absence of coordination at the regional level. This book shows that Atlanta's low-density urban form and its associated problems have been both highly coordinated and regionally planned. The author shows how regional policies spanned political boundaries and framed local debates over several decades in the city's history. The author explores four cases—regional land development plans, water supply strategies, growth management policies, and transportation infrastructure programs—to provide a detailed account of the interactions between citizens, planners, regional commissions, state government, and federal agencies.